PENGARUH PERTUMBUHAN PERUSAHAAN, KONDISI KEUANGAN, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP OPINI AUDIT GOING CONCERN - Dikdik Megantara (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2021)
This research was conducted with the aim of knowing how the influence of company growth, financial condition, company size and leverage on going concern audit opinion in manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2013-2017. The method used in this research is descriptive verification research. The population in this study amounted to 157 manufacturing sector companies in the study period from 2013-2017. The research sample was 98 companies in the manufacturing sector using purposive sampling method. Data obtained from the Indonesia Stock Exchange. The data analysis used in this research is multiple regression analysis. Analysis of research data processing using SPSS 25 software. The results of the research variable company growth have no effect on going concern audit opinion, financial conditions have no effect on going concern audit opinion, and company size has no effect on going concern audit opinion, while the leverage variable affects going concern audit opinion. Simultaneous testing shows that company growth, financial condition, company size and leverage have an effect on going concern audit opinion.